Religion as A Political Instrument to Maintain Power in The Wolf Hall - Tadzlila Hudna; Titis Setyabudi (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze how religion functions as a political tool to maintain and expand power in Hilary Mantel's novel Wolf Hall, focusing on narrative strategies and textual indicators that show the use of religion as a political instrument.Methodology: This study uses a descriptive qualitative approach with primary data in the form of dialogue, narrative descriptions, and character interactions in Wolf Hall (2009). Data were collected through intensive reading, text marking, thematic grouping, and supporting theoretical sources. The analysis combines Foucault's theory of the power of knowledge to interpret ideological control mechanisms and Abrams' theory of narrative elements to explore how character, plot, setting, and point of view are used to depict religion as a tool of political domination. Data validation follows the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion verification to ensure analytical accuracy.Results: The results show that religion in Wolf Hall functions as a strategic mechanism to restructure political authority, legitimize state power, build national identity, and shape collective obedience. The novel shows how religious discourse influences the psychological and social spheres, thereby enabling the consolidation of political control.Applications/Originality/Value: This research involves literary, political, and religious discourse studies, demonstrating how historical fiction reveals religion within power structures. This research explains the importance of Foucault and Abrams' theoretical frameworks for analyzing political narratives in literary works. This research can provide a reference for further studies on religion, ideology, and representations of power in narrative texts.